Ibn Sina on the Benefits of Worship to the Masses - Zakaria, Idris (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Ibn Sina in his most of his major writings focused more on the individual happiness. To achieve this, he demonstrate the important of performing ibadat (act of worship) such as al-Salat, where human souls are purified in order to ease the communication with Allah. This ibadat serves to remind people of God’s existence and of fate in afterlife as the salat (along with charity) is the investment in the hereafter. The act of worship must be repeated frequently and constantly and by this the remembrance of Allah becomes evergreen and beneficial to human being. This article discussed the benefit of worship to the masses according to Ibn Sina.